A phase 1b study evaluating the safety and pharmacokinetics of regorafenib in combination with cetuximab in patients with advanced solid tumors. Issue 9 (14th June 2019) - Weekes, Colin; Lockhart, A. Craig; Lee, James J.; Sturm, Isrid; Cleton, Adriaan; Huang, Funan; Lenz, Heinz‐Josef
Abstract : Regorafenib 160 mg orally once daily (QD) 3 weeks on/1 week off is approved in colorectal cancer, gastrointestinal stromal tumors and hepatocellular carcinoma. We established the safety and pharmacokinetics (PK) of regorafenib combined with cetuximab in advanced refractory solid tumors. This was a phase 1, open‐label, dose‐escalation study (NCT01973868) in patients with advanced/metastatic solid tumors who progressed after standard therapy. Regorafenib was administered at various dose levels QD continuously or intermittently (3 weeks on/1 week off) combined with intravenous cetuximab 250 mg/m 2 weekly. The primary objectives were safety, PK and maximum tolerated dose (MTD). The secondary objective was tumor response. Dose‐limiting toxicities (DLTs) were evaluated in Cycle 1. Of 42 treated patients, 31 received regorafenib intermittently (120 mg, n  = 8; 160 mg, n  = 23) and 11 continuously (60 mg, n  = 5; 100 mg, n  = 6) plus cetuximab. The continuous arm was terminated due to low tolerable dose. In the intermittent arm, one DLT (grade 3 hand–foot skin reaction) was observed at 120 mg but none at 160 mg, therefore 160 mg/day was declared as the MTD in combination with cetuximab. The most common all‐grade treatment‐emergent adverse events were fatigue (52%), hypophosphatemia (48%) and diarrhea (40%). One grade 3 cetuximab‐related dermatitis acneiform was observed. No clinically relevant drug–drug interactions were observed. Five patients (21%) had a partial response. Regorafenib 160 mg QD (3 weeks on/1 week off) plus standard dose of cetuximab was well tolerated with no unexpected toxicities and promising signs of efficacy. Abstract : What's new? Cancer treatment approaches frequently target protein kinases active in cancer cells, but resistance development limits long‐term success. In this phase 1b study, the authors combined two kinase inhibitors, regorafenib (oral) and cetuximab (intravenous), to overcome intrinsic and acquired resistance in epidermal growth factor receptor‐sensitive and ‐resistant tumors. The combination was well tolerated with no unexpected toxicities and promising initial signals of efficacy at the approved doses of both drugs in patients with advanced solid tumors.